2005
DOI: 10.1002/jso.20264
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of outcomes and survivals for two central venous access port systems

Abstract: We found infection, thrombosis occlusion, surgical complication, and actuarial device survival rates were similar between Deltec and Groshong groups. Hematogenous malignancy was a risk factor for catheter failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…Hou et al [10] reported these two catheter types had similar actuarial survival rates in their study. The Groshong catheter [12] has a unique three-way, pressuresensitive valve that allows infusion and blood aspiration while reducing risk of an air embolism, blood reflux, and clotting.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Hou et al [10] reported these two catheter types had similar actuarial survival rates in their study. The Groshong catheter [12] has a unique three-way, pressuresensitive valve that allows infusion and blood aspiration while reducing risk of an air embolism, blood reflux, and clotting.…”
Section: Discussionmentioning
confidence: 68%
“…The reported total adverse event rate was 5.1% (13/296 catheters) in the study by Dillon et al [13] , 11% (33/298 catheters) in the study by Hou et al [10] , 12.8% (192/1500 catheters) in the study by Kock et al [14] and 21% (14/66 catheters) in the study by Grannan et al [15] . There was a 7.5% (102/1348 catheters) total adverse event rate in the present series.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…15 Özel-likle literatürde hematolojik malignitelerin solid malignitelere göre cerrahi sonrası enfeksiyon oranının yüksek olduğu belirlenmiştir. 18 Genellikle kanser hastalarında tedavilere bağlı kemik iliği baskılanması, bağışıklık sisteminin zayıflaması ve kateter bakımının yetersizliğine bağlı olarak enfeksiyon gelişebilmektedir. Enfeksiyonlar genellikle iğne giriş yeri ve port cebi kökenlidir.…”
Section: Discussionunclassified